The Axiological Layers of the Internal Dialogue in the Armenian Mediatexts - PETROSYAN, DAVID (Bulletin of Yerevan University B: Philology, 2021)
Nowadays, mediatext related issues continue to remain in the center of researchers’ attention without losing their relevance. This context involves the study of the axiological layers of the internal dialogue. In the mediatext the internal dialogue begins with the author, whose “I” splits in the text revealing internal addressees. The author thus creates a unique theatrical environment and, through dialogical relations with internal addressees, prepares the entry of the text to the external audience. The letter of Ch. Chaplin and the essay of K. Surenyan are typical examples in this regard. The comparative analysis of these publications reveals a number of similarities and differences that generally reveal remarkable axiological layers in the internal dialogue of the mediatext-intellectual audience.